The Long Shadow of 9/11 America's Response to Terrorism - Jenkins, Brian Michael; Godges, John (RAND Corporation, 2011)
This book provides an array of answers to the question, In the ten years since the 9/11 attacks, how has America responded? In a series of essays, RAND authors lend a farsighted perspective to the national dialogue on 9/11's legacy; assess the military, political, fiscal, social, cultural, psychological, and moral implications of U.S. policymaking since 9/11; and suggest options for effectively dealing with the terrorist threat in the future.